ASEAN centrality: a bridge too far? - Anderson, Lawrence (2022)
Great power divisiveness is being generated outside the Southeast Asian region. ASEAN needs to rethink its assumptions, but it has many valuable elements in place. Great powers need to see the value of a non-partisan ASEAN, akin to a ‘bridge’ between their rival spheres, as essential for peace.